If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -102 + -7x = 10x + 14 Reorder the terms: -102 + -7x = 14 + 10x Solving -102 + -7x = 14 + 10x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10x' to each side of the equation. -102 + -7x + -10x = 14 + 10x + -10x Combine like terms: -7x + -10x = -17x -102 + -17x = 14 + 10x + -10x Combine like terms: 10x + -10x = 0 -102 + -17x = 14 + 0 -102 + -17x = 14 Add '102' to each side of the equation. -102 + 102 + -17x = 14 + 102 Combine like terms: -102 + 102 = 0 0 + -17x = 14 + 102 -17x = 14 + 102 Combine like terms: 14 + 102 = 116 -17x = 116 Divide each side by '-17'. x = -6.823529412 Simplifying x = -6.823529412
| 6y^2=12y | | x+5(x-4)=3(x-8)-5 | | 8v+9v=-6+1 | | 2x+6=-38-9x | | 22h+9=100 | | 4x-86=34 | | -34-2x=14-10x | | 11=u-8 | | 3y-5(y-1)=-5 | | 7+5x=52 | | 62-2x=16x+18 | | 7x+8=4-2x | | 8-7x=62-21x | | 4d+9e-d-3e= | | 14=u+7 | | 2x+3x^2+4=5 | | 4x+12=-72+8x | | -g=2.5g-(-3) | | 56x-4x=45 | | x^3-5x^2+5x-1=0 | | 3(0)+7y=21 | | 6x^2-42=0 | | 3x+7(0)=21 | | 2x+24=11x+84 | | 3x-12=11x-42 | | 17-x=11 | | 0=16(x^2)-7x-150 | | 4a+3=23 | | 12y-4=7 | | 5v^2-140=0 | | y(y+6)=0 | | 1+6y=6 |